THE EFFECTIVENESS OF THE SCIENTIFIC APPROACH ON THE CRITICAL THINKING SKILLS OF 5-6 YEAR OLD CHILDREN-A SYSTEMATIC LITERATURE REVIEW - Perisma Seri Saragih; Noviana Mustapa; Erie Siti Syarah; I Made Indra Purwanita (Fakultas Tarbiyah Universitas Ibrahimy Situbondo, 2025)
Critical thinking skills are essential skills that need to be developed from an early age to face the challenges of the 21st century. This study aims to assess the effectiveness of the scientific approach in improving the critical thinking skills of children aged 5-6 years through a systematic literature review. Data were collected from ten selected scientific articles published between 2020 and 2025 and analyzed based on strict inclusion and exclusion criteria. The study results show that the scientific approach significantly improves children's critical thinking skills, especially in the aspects of observing, questioning, reasoning, problem solving and concluding. This approach is effectively applied in various learning contexts, including conventional learning as well as those that integrate technology and innovative methods such as mind mapping, makerspace and problem-based learning. Successful implementation is strongly influenced by teacher competence, learning environment support, and parental involvement. However, challenges such as limited teacher understanding, lack of resources and low parental participation are still obstacles. Although its short-term effectiveness has been proven, longitudinal research is needed to assess its long-term impact on children's cognitive development. Thus, the scientific approach is recommended as the main learning strategy in early childhood education to optimally build the foundation of critical thinking.